Tidal Streams in the Local Group and Beyond: Observations and Implications - Newberg, Heidi Jo; Carlin, Jeffrey L. (Astrophysics and space science library, 2016)
Overview -- The Sagittarius Dwarf Tidal Streams – The Monoceros Ring and Substructure in the Galactic Anti center -- Tidal Tails and Clouds in Dwarf Galaxies and Globular Clusters -- Kinematically Detected Halo Streams -- The Cosmological Origin of Tidal Streams -- Detecting Dark Matter from Tidal Streams -- Tidal Streams in M31 -- Tidal Streams in Other Galaxies.
Includes bibliographical references and index
Keywords: Gravitationsströmung; Galaxie; Lokale Gruppe